Construction of a sustainable island city - Cruz, Rui Noel Alves Vera (2017)
The continental urban clusters followed models based on rules and standards that influenced the environment, which were in turn the result of consolidated growth and available technology. The successful models tend to be replicated, with examples seen in urban island clusters which adapted these guidelines, giving rise to a unique morphology resulting from models that à priori were not suited to the region. The urban fabric of these clusters maintained regular and sustainable growth until the last quarter of the 20th century, when the increase in immigration made it difficult to control the urban space. This phenomenon was responsible for the impact on the constructed as well as the social environment, resulting in the degradation of the quality of life for the communities. In the island regions, works were implemented in urban areas, using imported models, in the expectation of attaining a better quality of life. The constant changes that emerged in the cities of continental and insular regions, with the results observed deemed as excellent, encouraged entities in charge to follow guidelines that would foster social inclusion, although this led to a weakening of the local identity. This research focuses on the identification of the parameters that should constitute the basis for the construction of the sustainable insular city. The parameters identified were applied to two case studies related to two neighbourhoods on the northern outskirts of the city of Praia with different terrains with distinctly different characteristics in terms of their genesis, terrain and infrastructure systems. The application of the parameters resulted in the conclusion that it is possible to apply them to the local reality and that they are simple enough to be widely implemented in the context of developing insular countries.